2017
DOI: 10.17129/botsci.823
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination in <em>Ormosia macrocalyx</em>, an endangered tropical forest tree

Abstract: Background: Ormosia macrocalyx is a tropical forest tree classified as endangered. Its seeds experience problems of dispersion and apparent physical dormancy due to their hard seed coating. Hypotheses: 1) The stages of dehiscence of the fruits of Ormosia macrocalyx influence the germinative behavior of its seeds. 2) Pregerminative treatments will improve the germination process of the seeds stored under refrigeration. Study species: Ormosia macrocalyx Study site and period: Villahermosa, Tabasco, Mexico from O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…However, water uptake by O. paraensis seeds was observed after mechanical scarification due to integument rupture and a consequent exposure of parenchyma cells of the embryo cotyledon (Figures 1 and 2C-D). Vargas-Simón et al (2017) observed the highest percentages of germination in seeds of O. macrocalyx Ducke by means of mechanical scarification or its combination with gibberellic acid, which presented values of 68.0 and 61.3%, respectively.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…However, water uptake by O. paraensis seeds was observed after mechanical scarification due to integument rupture and a consequent exposure of parenchyma cells of the embryo cotyledon (Figures 1 and 2C-D). Vargas-Simón et al (2017) observed the highest percentages of germination in seeds of O. macrocalyx Ducke by means of mechanical scarification or its combination with gibberellic acid, which presented values of 68.0 and 61.3%, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…Because of their hardness and resistance, seeds of several Ormosia species are used for making handicrafts. However, this hardness hinders seed analysis and seedling production (Lopes et al, 2006;Gonçalves et al, 2011;Baigts, 2009;Teixeira et al, 2009;Basqueira et al, 2011;Curiel and Morais, 2011;Gurski et al, 2012;Silva and Moraes, 2012;Silva et al, 2014;Silva et al, 2015;Vargas-Simón et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, most researches on Ormosia species are mainly concentrated on tissue culture (He et al, 2015;Fan et al, 2011), seed reproductive ecology (Peng et al, 2009;Chen, 2016), seed germination (Vargas-Simón et al, 2017;Silva et al, 2014;Foster, 2008), seedling cultivation (Shen et al, 2009;Ye, 2014;Yang, 2011;Feng et al, 2007;Zhu et al, 2015), fertilization measures (Duan et al, 2017;Zheng, 2008) and forest afforestation techniques (Wu et al, 2009;Pan, 2004), while few studies have been performed on the growth rhythm of O. hosiei, O. xylocarpa and O. henryi from different provenances. Hence, this study is aimed to evaluate the growth rhythms and differences of the three species from different provenances for selecting the superior provenances of O. hosiei, O. xylocarpa and O. henryi for priority use and determining appropriate management technique.…”
Section: Introductionmentioning
confidence: 99%